Size and crystallinity control of two-dimensional porous cobalt oxalate thin sheets: tuning surface structure with enhanced performance for aqueous asymmetric supercapacitors. Issue 28 (29th June 2018) - Pu, Tao; Li, Jie; Jiang, Yuqian; Huang, Biao; Wang, Wensong; Zhao, Chenglan; Xie, Li; Chen, Lingyun
Abstract : Porous cobalt oxalate thin sheets with enhanced performance were synthesized under hydrothermal condition. Abstract : With excellent layered structures, abundant pores and a high specific surface area, two-dimensional (2D) porous nanostructured materials have been demonstrated to show great potential in supercapacitors. At present, it is highly desirable but remains challenging to prepare different sizes and crystallinity of 2D porous thin sheets so as to further improve the performance of supercapacitors. Herein, 2D porous cobalt-oxalate (Co-OA) thin sheets with different sizes and crystallinity assembled by interconnected nanosheet array frameworks have been successfully synthesized, using cobalt nitrate hexahydrate as a cobalt source and oxalic acid dihydrate as a ligand, through a simple hydrothermal strategy at 220 °C for different reaction times. The as-prepared sample at 220 °C for 20 h, has a high area specific capacitance (1.631 F cm −2 at the current density of 1.2 mA cm −2 ), good rate capability (80.6% retention upon increasing the current density from 1.2 to 12 mA cm −2 ) and excellent cycling performance (1.5% attenuation at 6.0 mA cm −2 for 2000 cycles). In addition, one aqueous asymmetric supercapacitor (ASC) is constructed based on the sample synthesised at 220 °C for 20 h as positive electrodes and activated carbon (AC) as negative electrodes. This ASC effectively provides a maximum energy density of 17.675 Wh kg −1 at 900 W kg −1, still maintaining 8.25 Wh kg −1 at 9000 W kg −1, which demonstrates it may be a promising candidate in energy storage for supercapacitors. It is worth emphasizing that this strategy could be extended to fabricate other materials with different sizes and crystallinity.